Lexical influences on predictive mouse cursor movements - Anuenue Kukona (Language and Cognition)
Two mouse cursor tracking experiments investigated lexical prediction. Participants heard predictive sentences (e.g., “What the librarian will read, which is shown here, is the…”) and viewed visual arrays with predictable targets (e.g., book) and phonological competitors (e.g., bull) or unrelated distractors (e.g., goat). Participants tasked with clicking on the (i.e., target) object referred to in sentences (Experiment 1), or with doing so interleaved with a cloze procedure (e.g., completing “What the librarian will read is this.”; Experiment 2), made predictive mouse cursor movements to targets. However, predictive attraction to phonological competitors was not observed. Implications for theories of predictive sentence processing are discussed.